Revisiting Infectious Complications in Hematopoetic Stem Cell Transplantation Recipients Who Receive Total Parenteral Nutrition. (4th October 2017) - Trifilio, Steven; Rubin, Halina; Fong, Jessica L; Greenberg, Deborah; Zhao, Cindy; Grushchak, Solomiya; Mehta, Jayesh
Abstract: Background: Older studies in hematopoetic stem cell transplantation recipients (HSCT), who receive parental nutrition (TPN) suggest a trend for increased risk of infection. An retrospective study was done to compare incidence, spectrum of infection, risk factors and clinical outcomes for patients who received TPN compared with those not treated with TPN during HSCT. methods. All HSCT recipients treated between 2005 and 2012 were included. All documented bacterial and fungal infections are included. Patients received at least 48 hour TPN. Results: In total, 1, 367 patients underwent HSCT including 197 who received TPN. There was no difference between groups for age ( P < 0.1428), gender ( P < 0.2455), diagnosis ( P < 0.0108) or allogeneic donor source ( P < 0.5006). Infection rates for autologous and allogeneic HSCT recipients treated with TPN were significantly higher for infections caused by Gram-positive, and Gram-negative organisms, polymicrobic and fungal infection, as well as the source of infection. Infection-related mortality was significantly higher in TPN treated patients. Risk factors for developing infection include receipt of an allogeneic HSCT ( P < 0.0354) number of TPN treatment days (<0.0001), and day post transplant TPN was initiated ( P < 0.0001). TPN patients with infection had increased mortality (<0.001) Conclusion: Stem cell recipients treated with TPN appear to be at increased risk for infection and mortality. Risk /benefit should be critically assessed before initiating TPN and limiting treatment duration, especially in allograft recipients may minimize infection risk. Disclosures: All authors: No reported disclosures.